New Advances in Nano-Drug Delivery Systems: Helicobacter pylori and Gastric Cancer - Zhu, Xiang; Su, Tingting; Wang, Shouhua; Zhou, Huiqing; Shi, Weibin (Frontiers in Oncology, 2022)
With the development of materials science and biomedicine, the application of nanomaterials in medical field is further promoted. In the process of diagnosis and treatment of diseases, a variety of drugs need to be used. It is an ideal state to make these drugs arrive at a specific location at a specific time and release at a specific speed, which can improve the bioavailability of drugs and reduce the adverse effects of drugs on normal tissues. Traditional drug delivery methods such as tablets, capsules, syrups and ointments have certain limitations. The emergence of new nano drug delivery system further improves the accuracy of drug delivery and the efficacy of drugs. It well known that the development of cancer of the stomach is the most serious consequences for the infection of h. pylori. For suffering from gastric cancer patients, the treatments are mainly surgery, chemotherapy, targeted and immune therapy, and other comprehensive treatments. Although great progress has been made, most of the patients in the first diagnosis has been late. Current treatments are of limited benefits for patients, resulting in a poor 5-year survival rate. Nanomaterials may play a critical role in early diagnosis. Nano-drug delivery system can signif-icantly improve the chemotherapy, targeted and immunotherapy of advanced gastric cancer, reduce the side effects of the original treatment plan, improve the therapeutic effect of tumor, and provide patients with better benefits. It is a promising treatment for gastric cancer. This article introduces the application of nanomaterials in the diagnosis and treatment of Helicobacter pylori and gastric cancer. And the development of new nano delivery systems.